Marianne meets the Mormons : representations of Mormonism in nineteenth-century France - Jensen, Heather Belnap; Cropper, Corry; Lee, Daryl (University of Illinois Press, 2022)
"In the nineteenth century, a fascination with the Church of Jesus Christ of Latter-day Saints made Mormons and Mormonism a common trope in French journalism, literature, politics, and popular culture. Heather Belnap, Corry Cropper, and Daryl Lee illuminate the creation and use of Latter-day Saint stereotypes in France from the 1830s to 1914. Though sometimes ridiculed, the Church of Jesus Christ of Latter-day Saints just as often played an important role in satire and criticism that exposed, critiqued, and parodied French society. France's extreme, imagined Mormonism became a malleable tool in debates over issues as diverse as family, Spiritualism, and church-state relations while providing artists and others with a medium for working through the possibilities and impossibilities of their own fragmented nation. Surprising and innovative, Marianne Meets the Mormons looks at how the Church of Jesus Christ of Latter-day Saints influenced generations of French public and intellectual life"--